2018
DOI: 10.3892/mmr.2018.8665
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and mitochondrial injuries differ following pneumoperitoneum pressure in rabbit models of varying degrees of hydronephrosis

Abstract: The influence of intraabdominal pressure which is necessary to maintain the operating area during the surgery cannot be ignored especially on the kidneys. Many articles have reported the effect of intraabdominal pressure on normal kidneys. However, the influence of intraabdominal pressure on hydronephrosis kidneys is rarely studied. The aim of the present study was to clarify whether intraabdominal pressure tolerance is modified in various degrees of kidney hydronephrosis by evaluating oxidative damage and mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Severe hydronephrosis leads to prolonged operating time in laparoscopic surgery, which may consequently lead to increased oxidative stress ( 38 ). Based on these facts and the observations of our previous study ( 16 ), it can be inferred that high-pressure CO 2 pneumoperitoneum may cause severe oxidative stress, mitochondrial injuries and even cell apoptosis in rabbit kidneys with severe hydronephrosis. Therefore, the present study examined the effects of high-pressure CO 2 pneumoperitoneum on kidneys with severe hydronephrosis and investigated the possible underlying mechanism.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Severe hydronephrosis leads to prolonged operating time in laparoscopic surgery, which may consequently lead to increased oxidative stress ( 38 ). Based on these facts and the observations of our previous study ( 16 ), it can be inferred that high-pressure CO 2 pneumoperitoneum may cause severe oxidative stress, mitochondrial injuries and even cell apoptosis in rabbit kidneys with severe hydronephrosis. Therefore, the present study examined the effects of high-pressure CO 2 pneumoperitoneum on kidneys with severe hydronephrosis and investigated the possible underlying mechanism.…”
Section: Discussionsupporting
confidence: 66%
“…In our previous study, the effect of pneumoperitoneum pressure on rabbit kidneys with no hydronephrosis, and with mild or severe hydronephrosis was investigated ( 16 ). The results indicated that severely obstructed kidneys have reduced cell tolerance to intraabdominal pressure, and that they are more likely to suffer oxidative damage and mitochondrial injuries when they were exposed to pneumoperitoneal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…ROS, MDA and T-SOD are important indexes for detecting oxidative damage and antioxidative damage in cells. 8 Compared with control group, ROS uorescence intensity and mitochondrial calcium uorescence intensity signicantly enhanced in si-Tmod1 group. Compared with si -Tmod1 group, shear group can signicantly reduce the increasement of ROS levels and calcium content produced by Tmod1 restrain (P < 0.05).…”
Section: The Inuence Of Shear On the Ros Mda T-sod And Content Of mentioning
confidence: 89%
“…CytC which is also released from dying cells during cellular trauma can act as a danger signal in the extracellular space. In experiments on rabbits, oxidative injury to mitochondria has been demonstrated to be associated with high mitochondrial expression of CytC [352]. In studies on a burn model in mice, circulating CytC levels were found to be elevated eightfold within 3 h post-injury and remained elevated at 24 h [353].…”
Section: Other Dampsmentioning
confidence: 97%